2005
DOI: 10.1677/erc.1.00896
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropins upregulate the epidermal growth factor receptor through activation of mitogen-activated protein kinases and phosphatidyl-inositol-3-kinase in human ovarian surface epithelial cells

Abstract: Gonadotropins, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) have been implicated as probable risk factors in epithelial ovarian carcinomas, most of which are derived from ovarian surface epithelium (OSE). Since epidermal growth factor (EGF) increases the growth of ovarian surface epithelial cells, we determined the effect of gonadotropins on the expression of epidermal growth factor receptor (EGFR). We investigated the basal levels of EGFR mRNA and protein, and the mechanisms involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 79 publications
(62 reference statements)
4
55
0
Order By: Relevance
“…These data indicate that in this model system, introduction of LHR up-regulates ErbB-2, that LH incubation in LHR-expressing cells further up-regulates ErbB-2, and that this up-regulation correlates with cAMP and IP3 accumulation, variables associated with LHR activation. Although some studies have linked FSH receptor overexpression to increased ErbB-2 expression (43) and others have shown an up-regulation of EGFR by both FSH and LH (13), the data presented here represent, to the best of our knowledge, the first demonstration that LHR expression and activation upregulate ErbB-2 protein expression.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…These data indicate that in this model system, introduction of LHR up-regulates ErbB-2, that LH incubation in LHR-expressing cells further up-regulates ErbB-2, and that this up-regulation correlates with cAMP and IP3 accumulation, variables associated with LHR activation. Although some studies have linked FSH receptor overexpression to increased ErbB-2 expression (43) and others have shown an up-regulation of EGFR by both FSH and LH (13), the data presented here represent, to the best of our knowledge, the first demonstration that LHR expression and activation upregulate ErbB-2 protein expression.…”
Section: Discussionmentioning
confidence: 46%
“…Epidemiologic evidence implicates the pituitary-derived gonadotropic hormones, follicle-stimulating hormone (FSH) and LH, in the development of ovarian cancer by correlating an increased risk of ovarian cancer with physiologic conditions resulting in increased exposure to LH and FSH, such as incessant ovulation, infertility treatments, and menopause (4,5). In vivo, LH influences cellular processes, including adhesion (6), apoptosis (7,8), anchorage-independent growth (9), angiogenesis (10), and proliferation in ovarian cancer cells or in ovarian epithelial cells, the putative precursor cell to epithelial ovarian cancer (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…FSH has also been shown to activate ERK and p38 mitogen-activated protein kinase (MAPK) in granulose cells [42,43]. Choi et al [44] found that FSH and LH activated MAPK and PI3K in human OSE cell. Additionally, FSH significantly upregulates the level of protein kinase Cα (PKCα) mRNA and protein, and the PKC pathway has been proposed to play a role in FSH-induced cell proliferation in ovarian cancer cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the observed effect on normal ovaries, FSH treatment is also reported to activate epithelial cell proliferation and oncogenesis in several human OSE immortalized normal, neoplastic (IOSE-29, IOSE-29E, and HOSE), and ovarian cancer cell lines (OVCAR-3 and OVCA) (Schiffenbauer et al 1997, Zheng et al 2000, Syed et al 2001, Choi et al 2004, Ji et al 2004, Abd-Elaziz et al 2005. Interestingly, this effect of FSH is associated with activation of MAPK/ERK rather than via the cAMP pathway (Choi et al 2002(Choi et al , 2005. Li et al (2007) showed that FSH acts on tumorigenic mouse ovary surface epithelium cell line ID8 via the growth factor-type receptor isoform (FSHR3) to bring about proliferation via calcium signaling and the ERK pathway -distinct from the canonical cAMP pathway associated with G protein-coupled FSHR1 isoform.…”
Section: R39mentioning
confidence: 96%